2022
DOI: 10.1186/s12909-022-03150-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative influence and performance analysis of virtual reality laparoscopic surgical training system

Abstract: Background Virtual reality (VR) surgery training has become a trend in clinical education. Many research papers validate the effectiveness of VR-based surgical simulators in training medical students. However, most existing articles employ subjective methods to study the residents’ surgical skills improvement. Few of them investigate how to improve the surgery skills on specific dimensions substantially. Methods Our paper resorts to physiological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…VR allows for the creation of realistic, interactive environments that can be used to train surgeons and other medical professionals, as well as to test new procedures and devices. Other research has shown that VR can be an effective tool for teaching surgical skills and for training healthcare professionals in laparoscopic surgery (Aoki et al, 2020; Gleason et al, 2022; Kamat et al, 2022; Mori et al, 2022; Yu et al, 2022) and neurosurgery (Petrone et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…VR allows for the creation of realistic, interactive environments that can be used to train surgeons and other medical professionals, as well as to test new procedures and devices. Other research has shown that VR can be an effective tool for teaching surgical skills and for training healthcare professionals in laparoscopic surgery (Aoki et al, 2020; Gleason et al, 2022; Kamat et al, 2022; Mori et al, 2022; Yu et al, 2022) and neurosurgery (Petrone et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Because the TIPS authoring environment allows SEs to build customizable VR lap scenarios, there is the opportunity for the creation of a range of cost-effective VR-training units with greater variety, specialization, and relevance, addressing the need for enhanced individualized deliberate practice 38,39 . Virtual reality remains a nascent field in surgical education, yet emergent research indicates that VR-based surgical simulators reduce cognitive load and encourage flow state, potentially translating to reductions in training time for skill acquisition 40 . We feel that the adaptability, trialability, and affordances offered by the TIPS provide significant opportunities for surgical educators and trainees.…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative analysis approach was also introduced to evaluate the VR training performance of surgical instruments such as laparoscopy. [133] Fifty-one participants wearing an ECG sensor were trained for four tasks through a VR laparoscopic surgery [126] Copyright 2018, Elsevier. c) Diagram of immersive manipulation through VR platform and holographic microscopy.…”
Section: Metaverse Platforms With Xr For Medical and Nursing Educationmentioning
confidence: 99%
“…d) Demonstration of VR laparoscopic surgery simulation. Reproduced with permission [133]. Copyright 2022, BMC.…”
mentioning
confidence: 99%